Static and Dynamic Tearing of Thin Steel Sheets - Aberkane, M.; Ouibrahim, A.; Pluvinage, G.; Azari, Z. (Проблемы прочности, 2003)
This paper presents the energy analysis of static mode III fracture of thin steel sheets. For dynamic tearing studies we used the Charpy test apparatus. Static tearing tests performed on three kind steel sheets indicate that the linear relationship of Mai and Cotterell is valid for specimens with a leg width W up to 30 mm. In the given range, the specific work of fracture Te is determined according to the Mai-Cotterell model. The Te kinetics is studied as a function of sheet thickness B, radius of curvature p, and loading rate V. The modified model includes a linear dependence of p versus W. Moreover, we show that variation of loading rate V from 1 to 300 mm/min has no effect on the specific work of fracture Te. A slight decrease in dynamic fracture toughness J0,d is found. Представлен энергетический анализ статического разрушения тонких стальных листов по типу KIII. При динамических испытаниях использовалось оборудование для образцов типа Шарпи. Статические испытания трех видов стальных листов на разрыв свидетельствуют, что линейное соотношение Мая-Коттрелла справедливо для образцов с шириной рабочей части до 30 мм. В указанном диапазоне удельная работа разрушения Ге определяется в соответствии с моделью Мая-Коттрелла. Исследовалась кинетика Ге в зависимости от толщины листа B, радиуса кривизны ρ и скорости нагружения V. Усовершенствованная модель включает линейное отношение ρ/W. Кроме того, изменение скорости нагружения V от 1 до 300 мм/мин показало, что удельная работа разрушения Ге не зависит от нее. Установлено незначительное снижение динамической трещиностойкости J0,d. Представлено енергетичний аналіз статичного руйнування тонких стальних листів за типом KIII . При динамічних випробуваннях використовувалось обладнання для зразків типу Шарпі. Статичні випробування трьох видів стальних дисків на розрив свідчать, що лінійне співвідношення Мая- Коттрелла справедливе для зразків із шириною робочої частини до 30 мм. У такому діапазоні питома робота руйнування Те визначається у відповідності з моделлю Мая-Коттрелла. Досліджувалась кінетика Те в залежності від товщини листа В, радіуса кривини ρ і швидкості навантаження V. Удосконалена модель включає співвідношення ρ/W. Окрім того , змінюючи швидкість навантаження V від 1 до 300 мм/хв, встановлено, що питома робота руйнування Те не залежить від неї. Показано незначне змeншeння динамічної тріщиностійкості J0,d.